Connecting the real world with the digital overlay with smart ambient media - Applying Peirce's categories in the context of ambient media - Lugmayr, Artur (Kluwer Academic Publishers, 2012)
This article is based on the keynote held at the workshop on Events in Multimedia (EiMM09) that took place in conjunction with the ACM Multimedia conference in Beijing in October 2009. The idea of the keynote was to develop and explain the idea of ambient media in general, it is principles, and additionally relate ambient media to information theoretical approaches such as Peirce's categories, to the theories of decision making, and to theories discussing how smart objects can be made 'smart' by simulating the human mind. This article rounds up with practical examples underlining the presented ideas and theories. © 2010 Springer Science+Business Media, LLC.